Seroprevalence survey of Chlamydophila abortus infection in breeding goats on commercial farms in northern Namibia - Crafford, Jan Ernst (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.